Blood pressure control and burden of treatment in South African primary healthcare: A cross-sectional study - Kevin Pender; Olufemi Omole (AOSIS, 2019)
Background: Poor blood pressure (BP) control has been associated with high burden of treatment (BOT) in several settings. It is not known whether this relationship holds true for South African primary care. Aim: The aim of this study was to assess BOT and determine its relationship with BP control amongst patients with hypertension in a large community health centre, south of Johannesburg. Setting: The setting of this study was carried out in the OPD of Johan Heyns Community Health Center. Methods: A cross-sectional study involving 239 patients with hypertension was carried out. Information on sociodemography and BP readings in the last 3 months were extracted from patient medical records. A researcher-administered treatment burden questionnaire was also used to collect information on participants' perceptions of BOT relating to medication regimen, navigating the healthcare system and life style changes and/or social and/or financial issues. Total BOT (TBOT) was determined as the sum of the scores in the three components and categorised as 1-45 = low, 46-90 = moderate and 91-140 = high. Analysis included descriptive statistics and test of association. Results: Most participants were white (54.2%), 55 years (52.9%), female (60.1%), married (56.3%), had grade 12 or more education (71.9%) and had no comorbidity (56.7%). The mean duration of hypertension treatment was 113.8 months and most participants were uncontrolled (60.1%). Most participants (75%) reported a low TBOT score, with a mean of 19.7. Amongst participants with clinical comorbidities, most (66.3%) did not consider hypertension to be more burdensome than other comorbid illnesses. There was no significant association between TBOT and BP control (p = 0.53). However, participants with a high BOT relating to medication regimen were significantly more likely to be uncontrolled (p = 0.04). Conclusion: Total BOT is low amongst study participants and has no significant influence on BP control. However, improvements in BP control in South African primary healthcare may be hinged on interventions that address problems associated with hypertension medication regimen.